REALISME MAGIS SERIAL NOVEL HOROR ANAK CREEPY CASE CLUB DAN IMPLIKASINYA DALAM PEMBELAJARAN BAHASA INDONESIA - Yudono, Kristophorus Divinanto Adi; Adhani, Agnes (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This research was conducted with two objectives, (1) to describe the content of magical realism in the children's horror novel series Creepy Case Club by Rizal Iwan, and (2) to describe the opportunities for using the book to support Indonesian language learning achievements in various learning phases. The approach used in this study is qualitative. Data is collected through documentation. The source of this research data is six children's horror novel series books Creepy Case Club by Rizal Iwan. Analysis is carried out by content or content analysis. The results of this study are (1) the children's horror novel series Creepy Case Club is a work of magical realism based on the existence of five magical realism markers that appear in each book, and (2) these six books can be used to support Indonesian language learning activities starting from phase A to phase F students. This book not only provides fear or tells stories about something that does not make sense but can also support the educational process of various Indonesian language learning materials.